KEPEMIMPINAN KEPALA SEKOLAH DALAM UPAYA MENINGKATKAN KEDISIPLINAN GURU - Rita Candra Kasih (UNIVERSITAS BENGKULU, 2016)
The objective of this study is to describe the roles of the school principal of his efforts to increase the teachers’ discipline. This research used a descriptive-qualitative method. The datawere gathered from the school principal, the teachers, the staff as well as the students. The results of this research show that the school principal has run his functions well. The indicator was that the school principal has successfully encountered the existing problems to increase the teachers’ discipline. The problems were the teachers’ lack of understanding about teaching administration, the lack of communication among the stakeholders in school. The school principal’s roles in this research are as educator, manager, supervisor, leader, innovator and motivator.Key words: leadership, discipline, principal